Functional Outcomes and Accuracy of Patient-Specific Instruments for Total Knee Arthroplasty. (October 2018) - Stone, Andrea H.; Sibia, Udai S.; MacDonald, James H.
Background. Patient-specific instruments (PSIs) were developed to improve mechanical axis alignment for patients undergoing total knee arthroplasty (TKA) as neutral alignment (180°) is a predictor of long-term success. This study examines alignment accuracy and functional outcomes of PSI as compared with standard instruments (SIs). Methods. We retrospectively reviewed a consecutive series of TKA procedures using PSI. A total of 85 PSI procedures were identified, and these were compared with a matched cohort of 85 TKAs using SI. Intraoperative decision-making, estimated blood loss, efficiency, Knee Society Scores, and postoperative radiographs were evaluated. Results. One hundred and seventy patients with comparable patient demographics were reviewed. Eighty-one percent of the PSI procedures were within target (180 ± 3°) mechanical alignment, while the SI group had 70% of cases within the target plane ( P = .132). Mean target alignment (2.0° PSI vs 2.2° SI, P = .477) was similar between groups. Twenty-seven percent of patients in the PSI group had surgeon-directed intraoperative recuts to improve the perceived coronal alignment. The change in hematocrit was reduced in the PSI group (8.89 vs 7.21, P = .000). Procedure time and total operating room time were equivalent. Knee Society Scores did not differ between groups at 6 months or at 1 year. Conclusion. Patient-specific instrumentation decreased change in hematocrit, though coronal alignment and efficiency were equivalent between groups. Surgeons must evaluate cuts intraoperatively to confirm alignment. Functional outcomes are equivalent for PSI and SI groups.